Militarizing the Border : When Mexicans Became the Enemy - Levario, Miguel Antonio, 1977- (Book collections on Project MUSE., 2012)
As historian Miguel Antonio Levario explains in this timely book, current tensions and controversy over immigration and law enforcement issues centered on the US-Mexico border are only the latest evidence of a long-standing atmosphere of uncertainty and mistrust plaguing this region. Militarizing the Border: When Mexicans Became the Enemy, focusing on El Paso and its environs, examines the history of the relationship among law enforcement, military, civil, and political institutions, and local communities. In the years between 1895 and 1940, West Texas experienced intense milita.